Pedigree Selection and Information Content. (26th April 2018) - Vardarajan, Badri N.; Beecham, Gary W.; Haines, Jonathan L.
Abstract: In this article, we discuss strategies for selection of families and family members for genetic studies. We will evaluate strategies to sample large families with multiply affected members, sibships, and nuclear families. In addition, we have added a section to discuss sub‐sampling within pedigrees for large sequencing studies, particularly when genome‐wide SNP chips are available on all members of a pedigree. The type of family sampled for a study will determine the statistical analyses and power of discovery of genetic findings. We will evaluate study designs that maximize power and allow for linkage and association analyses to identify genetic loci predisposing to phenotype. © 2018 by John Wiley & Sons, Inc.